Prevalence of Acinetobacter Species in Various Clinical Samples and its Antibiotic Sensitivity Pattern in Tertiary Care Hospital, Vadodara (GAIMS Journal of Medical Sciences, 2024)
Background: Acinetobacter species are Gram negative, non-fermentative bacteria commonly present in soil and water as free living saprophytes. They are isolated as commensals from skin and throat. Acinetobacter has emerged as an important nosocomial pathogen involved in outbreaks of hospital infections in hospitalized patients like septicaemia, pneumonia, wound sepsis, endocarditis, meningitis and urinary tract infections. Moreover, most of those outbreaks were caused by multi-drug resistant (MDR) strains of this organisms.Material and Methods: Various samples like blood, urine, swab, cerebro-spinal fluid (CSF), pleural fluid, body fluid, pus, catheter tip were taken from clinically suspected cases for culture and antimicrobial sensitivity testing. A total of 164 Acinetobacter species. were isolated from these samples, which were included in this study.Results: Out of 6555 culture positive isolates, 164 (2.50%) were Acinetobacter species. Out of total 164 isolates, 77% (126 isolates) were Acinetobacter baumannii and 23% (38 isolates) were Acinetobacter lwoffii. The rate of isolation of Acinetobacter was more in males (58%) & in infants (25%). Highest number of Acinetobacter species were isolated from the blood (30%) & from the Extramural-NICU (24%). Acinetobacter isolates from various samples other than urine samples show highest sensitivity to colistin (100%) & for urine samples, sensitivity to cotrimoxazole, cefotaxime, cefuroxime, levofloxacin and doxycycline was 25%. The prevalence of Acinetobacter spp in the present study is 2.50%.Conclusions: To prevent the spread of the resistant bacteria, it is critically important to have strict antibiotic policies while surveillance programmes for multidrug resistant organisms and infection control procedures need to be implemented.